Pemahaman Hadis tentang Maisir dan Relevansinya terhadap Judi Online: Analisis Pandangan Ulama Klasik dan Kontemporer - Azizi, Muhammad; Darta, Ali (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The phenomenon of online gambling, a modern form of gambling, has created serious social, economic, and moral problems. The practice can be analyzed through the concept of maisir, which is expressly prohibited in the hadith and the Quran due to its elements of betting, speculation, uncertainty, and destructive impact on individuals and society. This study aims to examine the hadith’s understanding of maisir by highlighting the views of classical and contemporary scholars and linking them to the relevance of the online gambling phenomenon. The research method used was qualitative with a thematic-comparative approach. The results show that classical scholars understand maisir as any form of betting-based transaction that negates fairness in exchange, thus being considered detrimental to spiritual and social values. Meanwhile, contemporary scholars expand the definition of maisir to modern phenomena such as online gambling, emphasizing aspects of financial loss, psychological addiction, technological exploitation, and moral degradation. The hadiths prohibiting maisir are considered relevant in the digital context because their principles are able to address the challenges of application-based gambling and online media. Furthermore, there are legal and social implications that Sharia regulations regarding maisir must be adapted to technological developments to protect society from the dangers of online gambling. The implications of this research are the importance of strengthening religious literacy in society, increasing the role of Islamic scholars and institutions in issuing fatwas and education regarding online gambling, and encouraging the government and legal authorities to integrate sharia principles with digital technology regulations.